Evaluation of interlayer bonding condition on structural response characteristics of asphalt pavement using finite element analysis and full-scale field tests. (15th October 2015) - Chun, Sanghyun; Kim, Kukjoo; Greene, James; Choubane, Bouzid
Highlights: Identify more realistic and effective method to characterize the different interlayer bonding behavior of layered flexible pavement system. Develop the improved three-dimensional viscoelastic finite element pavement model. Predict the effect of interlayer bonding condition on change in pavement critical responses. Measure the pavement critical response for pavement structures with different interlayer bonding conditions using full-scale field tests. Validate the applicability of the pavement model developed by comparing the responses predicted from the model with those measured from the field tests. Abstract: This study was primarily focused on evaluating the effect of different interlayer bonding conditions on change in critical responses for real pavements related to performance and service life using the results from the finite element analysis (FEA) and full-scale field tests. The current lack of thorough understanding and mechanistic characterization of the interlayer bonding behavior that enables to accurately simulate the change in structural responses of pavement system is probably the greatest deficiency in our ability to properly evaluate the effect of interlayer bonding condition for asphalt pavements. Also, most of the pavement models previously introduced assumed either full-bond or no-bond condition which is not a realistic interlayer condition for pavements in the field. Therefore, there is a need to develop improved model to accurately predict the change in pavement critical responses for real pavement system due to the different interlayer bonding conditions. Results indicated that the pavement model developed was capable of accurately predicting the change in pavement critical responses due to the different interlayer bonding conditions and the predicted values were matched well with those measured from the full-scale field test. Also, it was found that a good interlayer bonding condition can positively affect the strain responses of asphalt pavement that results in potential structural benefits for enhanced pavement performance. Based on the comparative observations between analytical and experimental results, it was confirmed that the interlayer bonding condition plays a significant role on structural response characteristics of layered flexible pavement system and therefore the pavement service life.